Obesity and Weight Change in Relation to Breast Cancer Survival - Chen, Xiaoli (2010)
The authors evaluated the prognostic effects of obesity and weight change after breast cancer diagnosis. A total of 5042 breast cancer patients aged 20–75 were identified through the population-based Shanghai Cancer Registry approximately 6 months after cancer diagnosis and recruited into the study between 2002 and 2006. Participants were followed by in-person interviews supplemented by record linkage with the Shanghai Vital Statistics Registry database. Anthropometric measurements were taken and information on sociodemographic, clinical, and lifestyle factors was collected through in-person interviews. During the median follow-up of 46 months, 442 deaths and 534 relapses/breast cancer-specific deaths were documented. Women with body mass index (BMI) ≥30 at diagnosis had higher mortality than women with 18.5≤BMI<25; the multivariate adjusted hazard ratios (HRs) were 1.55 (95% confidence interval (95% CI): 1.10–2.17) for total mortality and 1.44 (95% CI: 1.02–2.03) for relapse/disease-specific mortality. Similar results were found for pre- and post-diagnostic obesity. Women who gained ≥5kg or lost >1kg had higher mortality than those who maintained their weight. No association was observed between waist-to-hip ratio and mortality. Our study suggests that obesity and weight change after diagnosis are inversely associated with breast cancer prognosis. Weight control is important among women with breast cancer.